Gambaran Darah Ayam Kampung dan Ayam Petelur Komersial pada Kandang Terbuka di Daerah Tropis - Ulupi, N.; Ihwantoro, T. T. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
The aim of this research was to study the blood profile on kampung chicken and commercial laying hen that was reared in the open house of tropical zone. The study correlated with its level stress that caused by the high of rearing temperature. The kampung chicken and commercial laying hen, respectively 20 birds (32 week of aged) was used in this study. All of the chickens were placed in individual cage that has been providedrandomly in a pen. In the fourth week of the rearing was performed taking of blood sample to blood profile assays.The result showed that the profile of eritrocytes and leucocytes of kampung chicken were in the normal range physiologically. The value of hemotocrit, Mean Corpuscular Volume (MCV), and Mean CorpuscularHemoglobin (MCH) from commercial laying hen were lower than the normal range. The heterophiles/limphocytes value of kampung chicken (0.80) was lower than commercial laying hen (3.47). It can be concluded that kampung chicken was more healthy and more adaptive to the high rearing temperature in the open house of tropical zone.